Legal Analysis of the Use of Personal Identity as Guarantee in Online Loans - Reni Anggriani; Muhammad Raqi; Balqis Salma (Simbur Cahaya, 2025)
In the developing digital era, the practice of online lending has become a new thing among the public due to its ease and quick access. The use of ID cards as collateral in online lending has become an interesting topic in the legal context. This research aims to analyze whether ID cards can be categorized as documents that can be used as collateral. The research method used is a normative analysis of laws and regulations and other rules that can be used as a legal basis. Because basically ktp is a population document that functions as a means of identifying a person, not as proof of property ownership. However, in practice, personal identity/KTP is sometimes used as one of the requirements for obtaining online loans. This is done to verify the borrower's identity and minimize the risk of fraud. The analysis highlights various legal issues related to the use of ID as collateral in online lending, including aspects of consumer protection, contract validity, and legal liability in cases of identity misuse. This research provides a deep insight into the legal framework governing this practice as well as the challenges faced in law enforcement and consumer protection in the digital age.